1991
DOI: 10.1161/01.atv.11.4.1077
|View full text |Cite
|
Sign up to set email alerts
|

Relations of body habitus, fitness level, and cardiovascular risk factors including lipoproteins and apolipoproteins in a rural and urban Costa Rican population.

Abstract: Increased general and abdominal obesity has been independently associated with diabetes, increased risk of stroke, and coronary artery disease (CAD). It is more prevalent in developed countries and in urban areas of nonindustrialized nations than in less developed and rural areas. To evaluate the associations between general and abdominal obesity (as determined by total body fat, waist to hip ratio, umbilical to triceps ratio, and umbilical to subscapular ratio) with glucose, plasma lipoproteins, apolipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Both obesity and an unfavorable body fat distribution are associated with small, dense LDL in men and women from Costa Rica. 32 We have shown that the most important determinant of LDL size or pattern is the triglyceride concentration, with an overall correlation of -.628. This correlation was similar in Mexican Americans and non-Hispanic whites and was also similar in men and women.…”
Section: Discussionmentioning
confidence: 79%
“…Both obesity and an unfavorable body fat distribution are associated with small, dense LDL in men and women from Costa Rica. 32 We have shown that the most important determinant of LDL size or pattern is the triglyceride concentration, with an overall correlation of -.628. This correlation was similar in Mexican Americans and non-Hispanic whites and was also similar in men and women.…”
Section: Discussionmentioning
confidence: 79%
“…15 Triglyceride and HDL cholesterol levels are partially determined through genetic transmission, but environmental effects also play a substantial role. 19 - 23 A recent study of twin congruity in the National Heart, Lung, and Blood Institute Twin Study indicated no statistically significant differences in LDL size between the monozygotic and dizygotic twins. 18 The magnitude of change in LDL size in the present study was far greater than we had initially predicted.…”
Section: Discussionmentioning
confidence: 99%
“…The waist was de®ned as the narrowest circumference between the costal margin and the iliac crest, and the hip was de®ned as the widest circumference between the waist and the thigh. 23,24 Blood pressure was evaluated with a mercury sphygmomanometer in the left arm with the subject in a sitting position following a 5 min rest. Two readings were taken for each subject and the mean value used in analysis.…”
Section: Methodsmentioning
confidence: 99%